An Image Encryption Algorithm by Using Secure Key Generation Techniques - P. Prasanna; DR.K. Venkataramana (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This extension seeks to fortify the processes of security and authentication by integrating the Elliptic Curve Cryptography (ECC), for image encryption, with Local Binary Pattern Histogram (LBPH) for the authentication of live faces during registration and log-in. ECC is one of the measures that afford a greater degree of security with small key sizes, and it is thus brought in to encrypt images safely, responding to the compelling need for an efficient and lightweight image encryption technique, especially in resource-constrained environments. An image encryption algorithm is set up using ECC in such a way that visual data that is being transmitted and stored remain confidential, as opposed to the others, especially AES, which could work on heavier computational load. In addition, real-time face authentication will be done through the use of LBPH, meaning that users are allowed to authenticate themselves through facial recognition at the time of registration and log-in. This system depends on variants of LBPH, which are robust against lighting and facial expression variations, for face recognition consistent in varied environments. Thus, by merging ECC for image encryption with the LBPH method of face authentication, the extended version will further ensure confidentiality of the transmitted data and smooth and secure method of user authentication, further strengthening access control integrity. The enhanced system was analyzed for speed, accuracy, and efficiency and demonstrated significant improvements for real-time security applications.